APPROACHES TO CONDUCTING PRACTICAL CLASSES ОN ORGANIC CHEMISTRY FOR FUTURE PHARMACISTS IN THE PROFESSIONAL COLLEGE OF BSMU - Велика, Алла; Гарвасюк, Олександра; Кропельницька, Юлія (SWorldJournal, 2024)
In this article the main stages of conducting practical classes on organic chemistry and improvement of interactive learning methods for students-pharmasists of the professional college were considered. In our opinion, this method of teaching contributes